The problem of image segmentation and de-noising methods and various approaches to its solution - H.Shakah, Ghazi (International Journal of Engineering and Technology, 2019)
Image segmentation and de-noising are required to be used in digital image processing according to the recent since researches in this field, At present image de-noising and segmentation take part in real-world applications such as medical fields, computer vision, computer graphic, satellite, magnetic resonance imaging, computed tomography, single photon emission and computed tomography etc. These two methods are used for different images but mainly focus on medical images. In this paper provides an overview of the main classes of methods for segmentation of images, analysis of the effectiveness of their application and development prospects for the implementation of methods adaptive segmentation for the conditions of significant variations in the parameters of images. After that we present the comparison between segmentation techniques based on some specific parameters and find out suitable one.
Keywords: Image Segmentation; Image De-Noising; Medical Images; Assessment Methods; Structural Similarity; Non-Linear Method.